Governance structures, cultural distance, and socialization dynamics: further challenges for the modern corporation - Christian Cordes; Stephan Müller; Georg Schwesinger; Sarianna M. Lundan (Journal of Evolutionary Economics, 2022)
This paper relates cultural distance and governance structures. We suggest a model of cultural evolution that captures the idiosyncratic socialization dynamics taking place in groups of communicating and interacting agents. Based on these processes, cultural distance within and between groups or organizational units develops. Transaction cost theorists associate higher cultural distance with higher transaction costs. Therefore, one problem of economic organization is assessing alternative governance structures in terms of the socialization dynamics they enable that entail different intraorganizational transaction costs. Socialization governance structures that can be used to affect cultural distance among employees include shared social experiences in groups, the assignment of influential role models, group sizes, the recruitment of employees presocialized in certain ways, the recognition of specific cultural dimensions such as "individualism" or "collectivism", and the implementation of cooperative cultures in business units. These yield organizations differential capacities to adapt internal structures in transaction cost-minimizing ways.
Keywords: D21; D23; L25; M14; C61; 330; Cultural distance; Governance structures; Corporate culture; Cultural evolution; Firm performance